PERANCANGAN SISTEM INFORMASI PENJUALAN PAKAIAN WEGAH MANGAN MENGGUNAKAN CMS WORDPRESS BERBASIS WEB - Indah Tri Handayani; Hafidzah, Hafidzah (Jurnal Ilmiah Teknik, 2024)
The design of a web-based sales information system is a form of utilizing information and communication technology (ICT) in the economic sector. It is expected to facilitate financial transactions in a virtual marketplace, allowing buyers and sellers to meet and mutually benefit. The aim of this research is to develop a web-based application using WordPress CMS for the sale of ready-to-wear clothing at Wegah Mangan store. Based on the research conducted, it can be concluded that this application can be used as a ready-to-use online store. The development process involves several stages, including feasibility study, system analysis, planning, system design, and implementation. The result of this web-based clothing sales website at Wegah Mangan Online Clothing Store is expected to be one of the online shop making options that utilizes information technology and facilitates the sales and purchasing process between sellers and buyers according to the developments of the times.